2022
DOI: 10.3390/coatings12020253
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hydrophobic Nanostructured Antibacterial Coatings for Metallic Surface Protection

Abstract: A simple and cost-efficient method to modify different surfaces in order to improve their bioactivity, corrosion and wear resistance proved to be sol-gel coatings. The silane layers have been shown to be effective in the protection of steel, aluminum or magnesium alloys and copper and copper alloys. Moreover, it has been found that the adding of different inorganic nanoparticles into silica films leads to increasing their performance regarding corrosion protection. In this study, we fabricated, a simple sol-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The surface roughness of the rGO/Cu fabric was changed by the rGO sheets, and the hydroxyl and carboxyl groups of GO and cotton were removed during the reduction process by NaBH 4 31 , 32 . Surfaces with higher hydrophobicity have a stronger antibacterial effect 33 . Particularly, superhydrophobic surfaces have antibacterial adhesion properties, as they naturally possess nano/microscale structures in addition to the repulsion of water, which limits the access of bacteria on the surface 34 , 35 .…”
Section: Resultsmentioning
confidence: 99%
“…The surface roughness of the rGO/Cu fabric was changed by the rGO sheets, and the hydroxyl and carboxyl groups of GO and cotton were removed during the reduction process by NaBH 4 31 , 32 . Surfaces with higher hydrophobicity have a stronger antibacterial effect 33 . Particularly, superhydrophobic surfaces have antibacterial adhesion properties, as they naturally possess nano/microscale structures in addition to the repulsion of water, which limits the access of bacteria on the surface 34 , 35 .…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is not a bactericidal activity, but it uses the non-adhesion mechanism resulting in a reduction in viability of the bacteria on the surface. There were many researchers who investigated the effect of surface wettability (hydrophobicity [154,[215][216][217][218] or hydrophilicity [216,219,220]) on the bactericidal efficacy of nanostructured surfaces. Valiei et al studied the mechano-bactericidal efficacy of etched silicon nanopillars against P. aeruginosa bacteria.…”
Section: Factors Affecting Bactericidal Activity Of Mechano-bacterici...mentioning
confidence: 99%
“…Recent study showed that sol–gel coating technique can be used to coat metallic substrates containing monodispersed nanoparticles of Ag and Zn (sizes are in the range of 100–150 nm) with flower-like ZnO nanostructures. The rough surface texture of ZnO obtained from the sol–gel coating method displayed a superior hydrophobicity and liquid repellant properties to minimize biofilm formation [ 157 ]. The tribological and electrochemical behavior are another crucial factor in ZnO coating.…”
Section: Zno Coating Process and Technological Feasibilitymentioning
confidence: 99%